2018
DOI: 10.9758/cpn.2018.16.3.339
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Continuation-Maintenance Electroconvulsive Therapy on Reducing Hospital Re-Admissions in Patients with Treatment-Resistant Schizophrenia

Abstract: ObjectiveContinuation-maintenance electroconvulsive therapy (C/M-ECT) is used to prevent relapse or recurrence in patients with severe mental illnesses. We aimed to investigate the effect of C/M-ECT on reducing hospital re-admissions in patients with treatment-resistant schizophrenia.MethodsWe applied a mirror-image design by retrospectively examining re-hospitalization rates of 18 patients with schizophrenia spectrum disorders. We compared the numbers of psychiatric admissions during the actual period over wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Previous studies showed ECT as an effective treatment option for patients with TRS 39 40 41 . In addition, an RCT included in one of those previous meta-analyses demonstrated that ECT plus ziprasidone was not inferior to clozapine plus ziprasidone 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed ECT as an effective treatment option for patients with TRS 39 40 41 . In addition, an RCT included in one of those previous meta-analyses demonstrated that ECT plus ziprasidone was not inferior to clozapine plus ziprasidone 40 .…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this study conform to earlier studies exploring the number and duration of hospitalizations in heterogeneous diagnostic groups (Table 4). Most of the retrospective naturalistic studies were mirror-image studies, [23][24][25][26][27][28][29][30][31][32][33][34] whereas a few retrospective studies had control groups comprising patients taking maintenance pharmacotherapy. 28,30,35 These studies reported a lower number and shorter duration of hospitalization during mECT not only for patients with unipolar depression 30 but also for the patients presenting with depressive symptoms diagnosed as bipolar or schizoaffective disorder.…”
Section: Discussionmentioning
confidence: 99%
“…16 Although limited in number, studies reporting the efficiency of mECT in schizophrenia have been conducted lately. 25,34,40,41 Although limited data have been reported on schizophrenia, ECT augmentation in medication resistance has been recommended for patients with a partial response to clozapine or patients who cannot tolerate clozapine, which is shown to be effective in antipsychoticrefractory patients with schizophrenia. 10,40,42,43 Although prospective studies have failed to show a higher efficacy of mECT as monotherapy than that of pharmacotherapy for relapse prevention after the acute ECT, 44 they showed that mECT augmentation was associated with a longer time to relapse than pharmacotherapy alone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations